SALIVARY ALPHA-AMYLASE LEVELS MAY CORRELATE WITH CENTRAL SEROUS CHORIORETINOPATHY ACTIVITY. Issue 12 (December 2021) - Scholz, Paula; Altay, Lebriz; Sitnilska, Vasilena; van Dijk, Elon H. C.; Pereira, Alberto M.; van Haalen, Femke M.; Akhtar, Isha; Boon, Camiel J. F.; Fauser, Sascha
Abstract : Purpose: To investigate and compare the salivary alpha-amylase (sAA) activity as an indicator of the sympathetic activity and stress response in patients with central serous chorioretinopathy (CSC) and healthy control subjects. Methods: Prospective multicenter case series, including 80 CSC patients and 88 healthy control subjects. Central serous chorioretinopathy status was classified as either active or inactive, depending on the presence of subretinal fluid on optical coherence tomography. Salivary samples were collected in the morning from patients and control subjects of the main cohort and at midnight for the additional cohort. Salivary alpha-amylase activity was determined in all patients and control subjects. Results: Morning sAA activity was significantly higher in patients with active CSC compared with inactive CSC ( P = 0.049) and to healthy control subjects ( P = 0.012). There was no significant difference in sAA activity between patients with inactive CSC and control subjects ( P = 1.0). Nocturnal sAA activity did not show any significant difference between patients with active CSC and either inactive CSC or control subjects ( P = 0.139). Conclusion: Morning sAA activity is increased in patients with active CSC, although diurnal rhythmicity is preserved. Measurement of sAA is easy to perform and might be an eligible tool to further investigate the relation between stress and CSC. Abstract : Salivary alpha-amylase activity, as an indicator for sympathetic activity, is increased in patients with active central serous chorioretinopathy. Salivary alpha-amylase measurement could be helpful to further investigate the relation between stress and central serous chorioretinopathy.